2013
DOI: 10.3354/meps10347
|View full text |Cite
|
Sign up to set email alerts
|

Modeled distribution and abundance of a pelagic seabird reveal trends in relation to fisheries

Abstract: The northern fulmar Fulmarus glacialis is one of the most visible and widespread seabirds in the eastern Bering Sea and Aleutian Islands. However, relatively little is known about its abundance, trends, or the factors that shape its distribution. We used a long-term pelagic dataset to model changes in fulmar at-sea distribution and abundance since the mid-1970s. We used an ensemble model, based on a weighted average of generalized additive model (GAM), multivariate adaptive regression splines (MARS), and rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 76 publications
1
23
0
Order By: Relevance
“…Likewise, long-term, northward shifts in the distribution of seabirds have also been observed in the Bering Sea (Renner et al 2013, as well as the occurrence of new species farther north into the Chukchi Sea ). Additionally, long-term studies of seabird colonies in the Bering Sea indicate that food web changes may be more pronounced for near-surface foraging guilds compared to those foraging at depth .…”
Section: Seabird−prey Associationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Likewise, long-term, northward shifts in the distribution of seabirds have also been observed in the Bering Sea (Renner et al 2013, as well as the occurrence of new species farther north into the Chukchi Sea ). Additionally, long-term studies of seabird colonies in the Bering Sea indicate that food web changes may be more pronounced for near-surface foraging guilds compared to those foraging at depth .…”
Section: Seabird−prey Associationsmentioning
confidence: 97%
“…An examination of 4 decades of at-sea surveys showed that for northern fulmars, colony effect was a key factor in modeling the distribution of this highly abundant species in the SEBS (Renner et al 2013). Colony effect can vary among seabirds, however; diving seabirds, such as thickbilled murre, show a stronger colony effect than surface-feeding black-legged kittiwakes (Sigler et al 2012).…”
Section: Spatial Variability In Seabird Abundancementioning
confidence: 99%
“…Although tracking data is presence-only data, this analysis enables us to calculate a continuous density probability gradient (including near 0 values) spatially for use in our models. Bird density close to a breeding colony is stochastically high due to geometric spreading as birds commute to and from the island (i.e., colony effect; Ashmole and Ashmole 1967, Kinder et al 1983, Decker and Hunt 1996, Renner et al 2013, especially for central-place foragers, such as Streaked Shearwaters. The high density around the colony may not be a function of oceanic variables but merely a function of distance from the colony (Gre´millet and Boulinier 2009).…”
Section: Bird Trackingmentioning
confidence: 99%
“…For the tracking data, the normalized monthly data sets (April-July) were pooled into a single data set to fit and refine the model across seasons (Louzao et al 2009), as pooled data may be more representative of habitat use for a given species compared to monthly data alone. The performance of species distribution models may differ among modeling techniques used (e.g., Yen et al 2004, Oppel et al 2012, Renner et al 2013. In order to assess the predictive capacity of the various modeling techniques in estimating shearwater distribution, we compared shearwater tracking models from 2007 using four different modeling techniques: generalized linear model (GLM), generalized additive model (GAM), random forest, and an ensemble of all models (ensemble model).…”
Section: Habitat Modelingmentioning
confidence: 99%
See 1 more Smart Citation